Não somos selvagens: cultura política dos índios no Ceará (1799-1822) (We are not wild: Indian’s political culture in Ceará (1799-1822)) - Costa, João Paulo Peixoto (Cadernos de História, 2016)
O espaço social imaginado para os índios na América portuguesa, entre meados do século XVIII e início do XIX, os colocava em uma ambiguidade. Mesmo estando em situação de equidade com os brancos enquanto vassalos régios, eram caracterizados como ainda sujeitos a uma espécie de “menoridade moral”. Entre a construção da imagem dessa população associada à barbárie e a ação política dessas comunidades em suas povoações, chama atenção a procura constante dos índios em identificar-se enquanto súditos do rei e merecedores dos direitos que lhes eram garantidos e que bem conheciam. Diante desses conflitos, o objetivo é contrastar a imagem de “entregues à natureza” construída pelos governadores com a cultura política dos índios vilados no Ceará, omitida dos registros do governo, apesar de sua presença latente. Abstract The social space imagined for the Indians in Portuguese America, between the mid-eighteenth century and early nineteenth century, put them in an ambiguity. Even though they are in a situation of equality with the white men known as vassals, were characterized as still subject to a kind of "moral minority". Between the construction of the image associated with this barbarism and the political action of these communities in their towns’ population, it points out the constant pursuit of the Indians in order to identify themselves as subjects of the king and deserving of rights that were guaranteed and that they knew well. Given these conflicts, the goal is to contrast the image of “delivered to nature” which is built by the governors with the political culture of Indians in Ceará, that are omitted from the records of the government, despite its latent presence. Keywords: Indians. Political culture. Ceará.